Buccomaxillofacial Surgery and Traumatology in times of the COVID-19 pandemic: Management, risks and perspectives (Research, Society and Development, 2021)
Severe acute respiratory syndrome (SARS-CoV-2) is an infectious respiratory disease with significant morbidity and mortality rates evolving in 2020 as a Pandemic. Dentistry is classified in the high risk category because most procedures generate aerosols and oral and maxillofacial surgery is the dental specialty that performs functions both in the hospital and in the outpatient setting. The objective of the present work is to make an analysis of the management, risks and perspectives of oral and oral surgery and maxillofacial surgery in times of pandemic of COVID-19, since the elective surgeries must be suspended and the urgencies prioritized with the main objective of the management of the risks to avoid contagion in emergency care, however, regarding future perspectives, it is essential to adapt these professionals to the new reality of care due to the various procedures performed being of an urgent and emergency nature.